Network Pharmacology and Inflammatory Microenvironment Strategy Approach to Finding the Potential Target of Siraitia grosvenorii (Luo Han Guo) for Glioblastoma - Li, Juan; Bi, De; Zhang, Xin; Cao, Yunpeng; Lv, Kun; Jiang, Lan (Frontiers in Genetics, 2021)
Background: Glioblastoma (GB) is the most common and aggressive primary intracranial tumor of the central nervous system, and the prognosis of GB remains a challenge using the standard methods of treatment-TMZ, radiation, and surgical resection. Traditional Chinese Medicine (TCM) is a helpful complementary and alternative medicine. However, there are relatively few studies on TCM for GB. Purpose: We aimed to find the connection between TCM and anti-GB. Study design: Network pharmacology and inflammatory microenvironment strategy were used to predict Siraitia grosvenorii (Luo Han Guo) target for treating glioblastoma. Methods: We mainly used network pharmacology and bioinformatics. Results: CCL5 was significantly highly expressed in GB with poor prognostics. Uni-cox and randomForest were used to determine that CCL5 was an especially biomarker in GB. CCL5 was also the target for SG and TMZ. The active ingredient of Luo Han Guo - squalene and CCL5 showed high binding efficiency. CCL5, a chemotactic ligand, was enriched and positively correlated in eosinophils. CCL5 was also the target of Luo Han Guo, and its effective active integrate compound – squalene, might act on CCL5. Conclusion: SG might be a new complementary therapy of the same medicine and food, working on the target CCL5 and playing an anti-GBM effect. CCL5 might affect the immune microenvironment of GB.